Intra-vitam Diagnosis of Tuberculosis in Pigs: Concordance Between Interferon-Gamma Release Assay and Comparative Tuberculin Skin Test - Ippolito, Dorotea; Fiasconaro, Michele; Pruiti Ciarello, Flavia; Aliberti, Antonino; Vitale, Maria; Amato, Benedetta; Pasquali, Paolo; Di Marco Lo Presti, Vincenzo (Frontiers in Veterinary Science, 2020)
The role of pigs in the maintenance of bovine tuberculosis caused by Mycobacterium bovis has been demonstrated in many settings; however, the current control programs usually do not state any intra-vitam diagnostic procedure in this species, as for the cattle. Carcass inspection has shown to be insufficient to detect infection in swine; thus, the assessment of Intradermal Tuberculin test and Interferon-gamma release assay (IGRA) in this species is mandatory. The current study compares the performances of the Single Intradermal Comparative Cervical Tuberculin (SICCT) test and IGRA. A total of 628 Nebrodi Black pigs raised in free-roaming farms were subjected to the two tests simultaneously. Besides, 124 animals underwent to post-mortem examination for the detection of tuberculous lesions and isolation of mycobacteria from target organs. The two tests showed a concordance of 94,42% with a Cohen's k coefficient of 0,786 and McNemar chi-squared of 4.83 (P = 0.03). Slightly lower levels of concordance (90.32%) between SICCT and IGRA were obtained in the group of 124 animals, with a Cohen's k=0.797 and McNemar chi-squared value of 0.69 with a non-significant P=0.41. Moreover, the results showed how IGRA tends to result positive in higher rates, mostly when Non-Tuberculous mycobacteria (NTM) were isolated, suggesting a possible impairment of specificity in the event of co-infections in the swine. In conclusion, the results obtained support the possibility of the strategic use of IGRA or SICCT in combination or alternatively one to the other, particularly IGRA which showed lower specificity but has evident advantages over SICCT.